Bellman-Ford Algorithm for Shortest Path Selection - Afivah; Meira Perma Dewi (Rangkiang Mathematics Journal, 2025)
Determining the shortest path from one point to another (destination) is a problem often encountered in life. With the development of science and technology, the problem of finding the shortest path can be solved using various algorithms. The algorithm that is often used to find the shortest route is the Bellman-Ford algorithm. The Bellman-Ford algorithm requires initial location parameters and a destination as input to determine the shortest path. The algorithm's results provide the shortest distance along with the route from the initial location to the destination. Applying the Bellman-Ford Algorithm provides the shortest distance as a solution to the problem. This research determines the shortest path from the origin to the destination point, modeled by a weighted graph. The Bellman-Ford algorithm starts the iteration by updating the distance at each vertex if a shorter distance is found.